Transformations of French policy towards Iraq after 2014 (Nature and paths of interaction) (Tikrit Journal For Political Science, 2023)
Since 2014, French foreign policy towards Iraq has been characterized by a commitment to stability and security in the region. France has provided financial and military support to the Iraqi government in its fight against ISIS, while also engaging in diplomatic efforts to promote political reconciliation and economic development. France also sought to strengthen its bilateral relations with Iraq, especially in the areas of trade, energy and security. In addition, France has been actively involved in international efforts to address the humanitarian crisis in Iraq, providing aid and assistance to those affected by the conflict. French foreign policy towards Iraq has been guided by the desire to promote stability and security in the region, while also helping to ensure the long-term success of Iraq's transition to Democracy."
Keywords: - French politics - Towards Iraq - Political challenges - Foreign policy - After 2014